Comparing the NIS vs. MRC and INCAT sensory scale through Rasch analyses. Issue 3 (September 2015) - Draak, Thomas H. P.; Vanhoutte, Els K.; van Nes, Sonja I.; Gorson, Kenneth C.; Van der Pol, W.‐Ludo; Notermans, Nicolette C.; Nobile‐Orazio, Eduardo; Lewis, Richard A.; Léger, Jean‐Marc; Van den Bergh, Peter Y. K.; Lauria, Giuseppe; Bril, Vera; et al.
Abstract We performed a comparison between Neuropathy Impairment Scale‐sensory (NISs) vs. the modified Inflammatory Neuropathy Cause and Treatment sensory scale (mISS), and NIS‐motor vs. the Medical Research Council sum score in patients with Guillain‐Barré syndrome (GBS), chronic inflammatory demyelinating polyradiculoneuropathy (CIDP), and IgM monoclonal gammopathy of undetermined significance‐related polyneuropathy (MGUSP). The ordinal data were subjected to Rasch analyses, creating Rasch‐transformed (RT)‐intervals for all measures. Comparison between measures was based on validity/reliability with an emphasis on responsiveness (using the patient's level of change related to the individually obtained varying SE for minimum clinically important difference). Eighty stable patients (GBS: 30, CIDP: 30, and MGUSP: 20) were assessed twice (entry: two observers; 2–4 weeks later: one observer), and 137 newly diagnosed or relapsing patients (GBS: 55, CIDP: 59, and IgM‐MGUSP: 23) were serially examined with 12 months follow‐up. Data modifications were needed to improve model fit for all measures. The sensory and motor scales demonstrated approximately equal and acceptable validity and reliability scores. Responsiveness scores were poor but slightly higher in RT‐mISS compared to RT‐NISs. Responsiveness was equal for the RT‐motor scales, but higher in GBS compared to CIDP; responsiveness was poor in patients with MGUSP, suggesting a longer duration of follow‐up in the latter group of patients.